A case of Legionnaire’s endophthalmitis - Yu JH; Avaylon J; Kil H; Kim JK; Gallemore RP (International Medical Case Reports Journal, 2019)
Jea H Yu,1 Jaycob Avaylon,1 Hyein Kil,1 Jisoo K Kim,1 Ron P Gallemore1,21Department of Clinical Research, Retina Macula Institute, Torrance, CA, USA; 2Department of Ophthalmology, University of California, Los Angeles, CA, USAPurpose: To report a case of endophthalmitis associated with Legionella Pneumophila.Case Report: A 46-year-old, highly myopic male with a complex history of recurrent retinal detachments, macular hole, cataract surgery and an infected scleral buckle in the left eye, presented with pain, redness, hypopyon and vision loss in the left eye, 14 days following blunt head trauma. Empirical treatment for endophthalmitis with intravitreal injections of Vancomycin and Ceftazidime afforded minimal improvement. He developed recurrent hypopyon and underwent vitrectomy surgery with intravitreal antibiotic injections at the time of surgery and had improvement. Intraoperative culture was positive for Legionella Pneumophila. He had continued episodes of recurrent inflammation which were quelled by intravitreal moxifloxacin injections performed every 3–10 days. He developed a recurrent RD with proliferative vitreoretinopathy (PVR) and underwent vitrectomy with silicone oil. The retina was reattached but had no light perception vision in the affected eye.Conclusion: When endophthalmitis is contracted in a work-place setting, a culture for L. pneumophila should be considered. A combination of intravitreal moxifloxacin and oral azithromycin may be effective.Keywords: endophthalmitis, Legionella Pneumophila, Legionnaire’s disease